Introducing Walk-Alongs in Visitor Studies: A Mobile Method Approach to Studying User Experience. Issue 2 (3rd July 2018) - Skov, Mette; Lykke, Marianne; Jantzen, Christian
Abstract: This article introduces the walk-along method as a potential approach to study visitor interactions and experiences in situ. Prompted by the methodological challenges involved in gaining insight into the individual, subjective visitor experience, this article explores the potentials and pros and cons of the mobile, walk-along method. The mobile walk-along method is an open-ended qualitative approach to capturing visitors' immediate experiences, interpretations, and emotions in the instant of experiencing. This article points to the method's relevance in visitor studies by drawing on empirical and methodological insights from a visitor study at a science center exhibition about movement and health at the Experimentarium near Copenhagen, Denmark. Based on 34 group walk-alongs (108 visitors), the findings show that the walk-along method can provide an understanding of visitor experience related to visitors' spatial practice, personal biographies and the social architecture between visitors.